A study on customer retention towards frozen kuih pau, the product of Ainaz Food Processing Enterprise / Rozaini Abd. Halim - Abd. Halim, Rozaini (2013)
This research focused on Customer Retention towards Frozen Kuih Pau, the product of Ainaz Food Processing Enterprise. In this study, it examined the factors that have significant relationship with customer retentions towards Frozen Kuih Pau, the product of Ainaz Food Processing Enterprise. The three factors identified were price, trust and customer value. There were 170 questionnaires being distributed to current customers in northern region of this country but only 157 were useful. The sampling technique used was non probability sampling. Respondents were asked to rate their evaluation of price, trust & customer value on customer retention towards Frozen Kuih Pau, the product of Ainaz Food Processing Enterprise. Various data-analysis tools have been used to analyze the data such as frequency analysis, reliability analysis, Pearson’s Correlation and Multiple Regression analysis. As a whole, the factors identified were found to be significantly related to customer retention towards Kuih Pau, the product of Ainaz Food Processing Enterprise. Hopefully this study will provide Ainaz Food Processing Enterprise an idea in creating its marketing strategy in order to retain customers towards its Frozen Kuih Pau product.